Petersen hernia - Pomi, Jorge; Balboa, Oscar (Cirugía del Uruguay, 1977)
A patient who had undergone gastrectomy Billroth II 10 years previously, presented Petersent's herniation with necrotic jejunal loop. Etiopathogeny and prophylaxis of this condition are discussed.